Dynamics of Islamic Banks in the Digital Transformation Era - Ardana, Yudhistira; Khofifah, Anggita Nur; Lestari, Dewi Puji (Al-Mashrof: Islamic Banking and Finance, 2023)
Islamic banking has developed significantly over the past four decades and today has a global reach. One of the factors hindering Islamic banking in the coming decades is in the realm of financial technology (known as Fintech). Traditional financial methods will be abandoned in the digital age. This study will discuss the topic of financial innovation and technology in Islamic finance, as well as its Islamic parameters. This study employs qualitative secondary techniques using inductive methods to investigate primary data and on the topic, as well as descriptive methods to characterize the growth of fintech in the operations and practices of the Islamic banking industry. Based on the results of the study in this study, all innovations in Islamic finance need to be appreciated and can be seen as benefits (maslahah) for users (customers) and the financial industry as a whole. The results of this study also emphasize the relationship between fintech and shariah compliance which then recommends putting in place a comprehensive shariah governance framework to ensure that fintech operations are fully shariah compliant. Furthermore, authorities and regulators should adopt shariah standards that specifically identify shariah identifications that are important to fintechs.